Comparative effectiveness of different treatment modalities for active, moderate‐to‐severe Graves' orbitopathy: a systematic review and network meta‐analysis. Issue 6 (16th December 2021) - Li, Hongxun; Yang, Lihong; Song, Yi; Zhao, Xinheng; Sun, Chunhua; Zhang, Lei; Zhao, Hong; Pan, Ye
Abstract: To compare the effects of different treatment modalities on active, moderate‐to‐severe Graves' orbitopathy (GO). We searched PubMed and Embase for randomized controlled trials published up to 30 Nov 2020, of different modalities for the treatment of active, moderate‐to‐severe GO. We performed Bayesian network meta‐analyses. This study is registered with PROSPERO (CRD42020166287). Fifteen RCTs were identified. Network meta‐analysis showed that in comparison with placebo, teprotumumab, mycophenolate plus intravenous glucocorticoids (IVGCs), mycophenolate, rituximab, azathioprine, IVGCs, orbital radiotherapy, oral glucocorticoids (OGCs) were effective treatments (ordered from most effective to least effective). Teprotumumab was more efficacious in reducing proptosis than IVGCs. No significant difference in changes in diplopia grade was recorded between teprotumumab, rituximab, orbital radiotherapy and IVGCs. Low (4.5–5 g), middle (6 g) and high (7–8 g) cumulative doses of IVGCs were shown to be more effective than OGC in improving the overall response rate, but the very low‐group (<3 g) seemed to have a lower risk of adverse events. We found that teprotumumab offered the highest level of efficacy in terms of the overall response rate and was more efficacious in reducing proptosis than IVGCs. With regard to different dosages of IVGCs, the cumulative dose of 4.5–5 g of IVGCs seems to be the most appropriate schedule in terms of efficacy and safety outcomes. Due to the limited number of patients treated with teprotumumab and the lack of comparison with other effective therapeutics, teprotumumab might not become the standard first‐line therapy for active, moderate‐to‐severe GO.